Insights into the formulation properties, biocompatibility, and permeability of poorly water-soluble methoxyflavones with PEG400 and propylene glycol - Eze Fredrick Nwude; Jansakul Chaweewan; Srichana Teerapol (Acta Pharmaceutica)
Herein, thermal and non-thermal techniques were used to elucidate the putative physical and chemical interactions between poorly water-soluble Kaempferia methoxyflavones and PEG400/propylene glycol. Additionally, the biocompatibility of methoxyflavone-glycol solutions was evaluated using Caco-2 cells whereas the absorptive transport was investigated by measuring the apparent permeability coefficient (Papp) of the methoxyflavones and transepithelial electrical resistance (TEER) of the Caco-2 cell monolayer. Data from differential scanning calorimetry, Fourier-transform infrared (FTIR), and proton nuclear magnetic resonance (1H NMR) spectroscopic analysis revealed physico-chemical compatibility between the three methoxyflavones and PEG400/propylene glycol. Furthermore, PEG400 and propylene glycol solutions of the methoxyflavones were shown to be compatible with Caco-2 cells at pharmacologically effective concentrations. In vitro transport studies across the Caco-2 cell monolayer revealed high Papp values of 24.07 × 10–6 to 19.63 × 10–6 cm s–1 for PEG400 solutions of the methoxyflavones. The TEER values of the Caco-2 cell monolayers indicated that the increased drug transport was partly due to increased tight junction openings, but without compromising the epithelial barrier integrity. The good pharmaceutical and biocompatibility profiles, as well as improved transport of the methoxyflavones in PEG400 and propylene glycol solutions, are suggestive of the worthiness of this approach for further consideration pertaining to the development of these drugs into oral liquid dosage forms.